Two new species of the genus Odontoscion (Teleostei: Sciaenidae) from the Western Atlantic Ocean - Carvalho-Filho, Alfredo; Gasparini, João Luiz; Duarte, Luiz; Pfliger, Jonathan; Sampaio, Cláudio L. S.; Araujo, Gabriel Soares (Zootaxa, 2026)
Three species of reef croakers (Teleostei: Sciaenidae: Odontoscion) are recognized to date, two from the Pacific and one from the Atlantic. Odontoscion dentex (Cuvier) was previously the only species in the Atlantic, known from Florida, Cuba, and the Caribbean to Southeastern Brazil. Here, we describe two new species of Odontoscion from the Western Atlantic based on the mitochondrial cytochrome c oxidase I gene and morphological characters. One species, O. pepojuba sp. nov., inhabits Brazilian coastal waters from the states of Pará to Santa Catarina; the other one, O. pitassyae sp. nov., is known from Trinidad & Tobago and Dominica. A fourth putative species from Florida, labeled here as O. dentex lineage B is also proposed, but yet to be described. The diagnostic characters of the genus are also revised.